FIRST REACTIONS OF THE PARENTS OF CHILDREN WITH DEVELOPMENTAL DISORDERS (Annual of the Faculty of Philosophy in Skopje, 2015)
When the parents for the first time find out that their child has some developmental disabilities, their lives change instantly and they have to face many challenges. Above all, they have to change their expectations about the child, which they have set before, have to cope with the additional financial costs (payment of drugs, additional treatments, private lessons, transport), as well as numerous absences from the work or to quit the job, because someone has to take care of the child with developmental disabilities. Some of them may experience a social isolation by the family, neighbors and friends.The reactions of the parents during the diagnosis of their child are exclusively individual, so their knowledge is crucial for the process of the rehabilitation, because it will depend a lot from the parents ’ attitude. The intensity and the manifestation of the reaction depend of the: personality of the parent, parent's aspiration about the child, deviations in the family, socio-economic status of the parents and etc.The most common reactions of the parents, when they first time confronted with the fact that they have a child with developmental disabilities are: shock, denial, anger, fear, shame, guilt, confusion, powerless, disappointment, indignation, jealousy and sorrow.